2021
DOI: 10.1101/2021.02.15.21251586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology of COVID-19 infection amongst workers in Primary Healthcare in Qatar

Abstract: Background: COVID-19 transmission was significant amongst Healthcare workers worldwide. Aim: This study aims to estimate the risk of exposure for COVID-19 across Primary Healthcare workers in the State of Qatar. Methods: A cross-sectional descriptive study was conducted to study the burden of COVID-19 among staff working at PHCC during the COVID-19 pandemic from March 1 to October 31, 2020. Results: 1,048 (87.4%)of the infected HCWs belonged to the age group below 45 years, and 488 (40.7%) HCWs were females.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Hypertension and diabetes mellitus were the main co-morbidities observed while the manifested symptoms were generally non-specific with fever, sore throat and cough being most common followed by tiredness/ aches, respiratory symptoms, and headaches. Accordingly, our results are consistent with published data from Qatar on HCWs [22,23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hypertension and diabetes mellitus were the main co-morbidities observed while the manifested symptoms were generally non-specific with fever, sore throat and cough being most common followed by tiredness/ aches, respiratory symptoms, and headaches. Accordingly, our results are consistent with published data from Qatar on HCWs [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…In this observational study, we have explored and described the clinical characteristics, laboratory parameters and radiological features of SARS-COV-2 infection in HCWs in governmental hospitals in Qatar. There are two published papers from Qatar focused primarily on prevalence of SARS-COV-2 infection and risk factors in healthcare workers (HCWs) [22,23]. This study provides an in-depth analysis of the demographics, clinical characteristics as well as correlation of changes in lab parameters with CXR severity in HCWs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were six studies from the United States [10,12,19,24,25,31], six studies from India [16,18,20,27,29,32], two studies from the United Kingdom [17,26], two from Egypt [21,30], one each from Brazil [22], Chile [28], Ethiopia [33], Iran [15], Mexico [14], Qatar [11], Saudi Arabia [13] and Turkey [23].…”
Section: Figure 1 Prisma Flowchart Illustrating the Study Selection P...mentioning
confidence: 99%
“…The seroprevalence studies, with the exception of a single study from Iran [15], consistently reported that environmental services workers (housekeeping, cleaners and janitorial staff) were at a significantly elevated risk of having contracted COVID-19 compared to other healthcare workers in the same institution [10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28]. The quality of these cross-sectional studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal checklist for analytical cross-sectional study [34] by consensus among three study investigators (Q.X.N., C.Y.L.Y.…”
Section: Figure 1 Prisma Flowchart Illustrating the Study Selection P...mentioning
confidence: 99%